PRICE TRANSMISSION OF SKIM MILK POWDER IN INDONESIA: DO SKIM MILK POWDER IMPORT PRICES FOLLOW THE PRICES IN NEW ZEALAND? - Venty Fitriany Nurunisa; Bonar Marulitua Sinaga; Ratna Winandi; Bernhard Brummer (Forum Agribisnis, 2014)
The objectives of this research are i) to examine New Zealand's dairy sector and ii) to analyze the market integration and price transmission of Skim Milk Powder (SMP) of New Zealand and Indonesian market. The methods used are Augmented Dickey Fuller test, Johansen Cointegration test, and Vector Error Correction Model. The result indicates: 1) as trade partner, New Zealand is powerful due to its status as the largest dairy producer worldwide; therefore, Indonesia has less bargaining power and 2) The SMP market of both countries are integrated. The coefficient of long run equation variable indicates that every 10 percent changes of one market, the imported SMP price will adjust 10.97 percent, while the exported SMP price will adjust 9.12 percent. The loading vector coefficient indicates that Indonesia is the only party adjusting to long run disequilibrium. Policies to minimize the risks includes: i) buffer budget, ii) alternative suppliers and iii) futures trade.